APPLICATION OF ADDITIONAL CORRECTIVE CRIMINAL PENALTIES IN ENVIRONMENTAL CRIMES ( CASE STUDY OF BALIGE DISTRICT COURT DECISION NO. 28 /PID.SUS/201 5 /PN .BLG ) - Tabroni (Cattleya Darmaya Fortuna, 2025)
The background of this research is the increasing threat to environmental sustainability due to human activities. Law Number 32 of 2009 concerning Environmental Protection and Management (UUPPLH) serves as the legal basis, which allows for the imposition of principal and additional criminal sanctions on business entities committing environmental crimes. The case in question involves PT. Gorga Duma Sari (PT. GDS), where its president director, JONNI SIHOTANG, was accused of environmental damage through tree felling and land clearing without permits and valid environmental documents, causing damage to the river ecosystem. Although the Public Prosecutor did not demand additional remedial penalties, the Panel of Judges at the Balige District Court in its decision imposed additional penalties on PT. GDS to repair the environmental damage. This decision was based on the consideration that the crime was committed for the benefit and profit of PT. GDS, as well as the application of the principles of